Religious Priming: A Meta-Analysis With a Focus on Prosociality. (February 2016) - Shariff, Azim F.; Willard, Aiyana K.; Andersen, Teresa; Norenzayan, Ara
Priming has emerged as a valuable tool within the psychological study of religion, allowing for tests of religion's causal effect on a number of psychological outcomes, such as prosocial behavior. As the literature has grown, questions about the reliability and boundary conditions of religious priming have arisen. We use a combination of traditional effect-size analyses, p -curve analyses, and adjustments for publication bias to evaluate the robustness of four types of religious priming (Analyses 1-3), review the empirical evidence for religion's effect specifically on prosocial behavior (Analyses 4-5), and test whether religious-priming effects generalize to individuals who report little or no religiosity (Analyses 6-7). Results across 93 studies and 11, 653 participants show that religious priming has robust effects across a variety of outcome measures—prosocial measures included. Religious priming does not, however, reliably affect non-religious participants—suggesting that priming depends on the cognitive activation of culturally transmitted religious beliefs.